1992
DOI: 10.1042/bj2810401
|View full text |Cite
|
Sign up to set email alerts
|

Wheat and barley allergens associated with baker's asthma. Glycosylated subunits of the α-amylase-inhibitor family have enhanced IgE-binding capacity

Abstract: A 16 kDa protein, designated CM16*, which strongly binds IgE from baker's-asthma patients has been identified as a glycosylated form of the previously reported WTAI-CM16, which is a subunit of the wheat tetrameric alpha-amylase inhibitor. A glycosylated form (CMb*) of BTAI-CMb, the equivalent inhibitor subunit from barley, has been also found to have significantly enhanced IgE-binding capacity. In all, 14 purified members of the alpha-amylase/trypsin-inhibitor family showed very different IgE-binding capacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 24 publications
6
90
2
Order By: Relevance
“…18) Tri a Bd 17K was identified asamylase inhibitors, CM16 and CM17, with Asn-linked sugar chains. 18) Tri a Bd 36K has peroxidase activity and is highly homologous with barley peroxidase BP1, 20) which indicates that Tri a Bd 36K is a peroxidase. 21) Sanchez-Monge et al 22) reported this allergen y To whom correspondence should be addressed.…”
Section: Isolation and Molecular Cloning Of A Major Wheat Allergen Tmentioning
confidence: 99%
“…18) Tri a Bd 17K was identified asamylase inhibitors, CM16 and CM17, with Asn-linked sugar chains. 18) Tri a Bd 36K has peroxidase activity and is highly homologous with barley peroxidase BP1, 20) which indicates that Tri a Bd 36K is a peroxidase. 21) Sanchez-Monge et al 22) reported this allergen y To whom correspondence should be addressed.…”
Section: Isolation and Molecular Cloning Of A Major Wheat Allergen Tmentioning
confidence: 99%
“…However, their IgE-binding capacities in vi tro are very different . In wheat and barley the glycosylated forms of WTAI-CM16, BTAICMb and BMAI-1 have been found to be the most prominent allergens, both in vi tro and in vivo (García-Casado et al, 1995;Sanchez-Monge et al, 1992). cDNA clones encoding these three proteins have also been isolated (García-Maroto et al, 1990;Medina et alA993;Mena et al, 1992).…”
Section: Allergenic Propertíesmentioning
confidence: 99%
“…Most of these inhibitors isolated from wheat, barley and rice are recognized by specific IgE when tested with sera from allergic patients (Barber et al, 1989;García-Casado et al, 1995;Gómez et al, 1990;Izumi et al, 1992;Sanchez-Monge et al, 1992;1996a,b). However, their IgE-binding capacities in vi tro are very different .…”
Section: Allergenic Propertíesmentioning
confidence: 99%
“…Extensive studies identified some proteins as allergens associated with asthma. Among them, alpha-amylase inhibitors (AI) from globulin fraction were identified as major allergens (3)(4)(5)(6). Acyl-CoA oxidase (7,8), peroxi dase (9), and fructose-bisphosphate aldolase (8) were identified as other allergens.…”
mentioning
confidence: 99%